2010
DOI: 10.1055/s-0029-1240655
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Patients Awaiting Heart Transplantation

Abstract: The aim of this study is to provide a description of patients on the waiting list for heart transplants in Germany; the focus is on comparing the era after implementation of the new transplant law with the former era. This study used data from the Eurotransplant registry. The population consisted of all patients who registered for heart transplantation in Germany between January 1990 and May 2009. Patients were followed up to the earliest of the following events: heart transplantation, death, or end of the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Smits et al demonstrated that the accrued waiting time on the waiting list for HTx has risen dramatically. While in 1990, 84.6 % of all patients had a waiting time shorter than 1 year, this proportion had decreased to 68.8 % in 1997 and had dropped to 37.8 % in 2008 [10]. In addition, Smits reported that a roughly constant number of new registrations for patients requiring HTx in Germany since 2003 faces a decreasing number of HTx performed over the last 10 years (1997: 526 HTx; 2000: 402 HTx; 2008: 346 HTx) [10].…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Smits et al demonstrated that the accrued waiting time on the waiting list for HTx has risen dramatically. While in 1990, 84.6 % of all patients had a waiting time shorter than 1 year, this proportion had decreased to 68.8 % in 1997 and had dropped to 37.8 % in 2008 [10]. In addition, Smits reported that a roughly constant number of new registrations for patients requiring HTx in Germany since 2003 faces a decreasing number of HTx performed over the last 10 years (1997: 526 HTx; 2000: 402 HTx; 2008: 346 HTx) [10].…”
mentioning
confidence: 95%
“…While in 1990, 84.6 % of all patients had a waiting time shorter than 1 year, this proportion had decreased to 68.8 % in 1997 and had dropped to 37.8 % in 2008 [10]. In addition, Smits reported that a roughly constant number of new registrations for patients requiring HTx in Germany since 2003 faces a decreasing number of HTx performed over the last 10 years (1997: 526 HTx; 2000: 402 HTx; 2008: 346 HTx) [10]. This is presumably aggravated by the dramatic shortage of donor organs in Germany, where the number of multiorgan donors per million of the population is very low: 15.9 in Germany compared with 34.3 in Spain, 28.2 in Belgium, and 25.3 in France.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Sin embargo, existe un grupo de enfermos refractarios que avanzan irremediablemente a insuficiencia cardiaca terminal (ICT), cuya única alternativa terapéutica es el trasplante cardiaco 3,4 . Desafortunadamente, es una opción limitada por el escaso número de donantes y muchos mueren esperando un órgano 5 . Recientemente, la asisten-cia ventricular (AV) extra o intracorpórea emerge como una alternativa terapéutica viable para pacientes con ICT, permitiendo su sobrevida hasta ser trasplantados 6 .…”
unclassified
“…Heart transplantation remains one of the gold standards for the treatment of end-stage heart failure, irrespective of whether heart failure has resulted from coronary artery disease, congenital heart defects or progressive cardiomyopathy. However, peopleʼs willingness to donate organs is still low [1,2] and reducing graft rejection rates is therefore of the utmost importance. Besides immunologically modulated graft rejection, vascular graft failure represents the most frequent late cause of death after heart transplantation [3].…”
mentioning
confidence: 99%